2020
DOI: 10.14232/iskkult.2020.7.46
|View full text |Cite
|
Sign up to set email alerts
|

Az Észlelt Tanári Kiégés Kérdőív szerkezetének vizsgálata középiskolás diákok körében

Abstract: Háttér és célkitűzések: A burnout-szindróma számos módon kapcsolódik az iskolapszichológiai kutatásokhoz. A pedagógusok és a diákok körében egyaránt magas a kiégés aránya, ami súlyos egyéni pszichológiai problémák kialakulásához vezethet. Mindemellett számos kutatási eredmény támasztja alá, hogy a diákok motivációját, viselkedését befolyásolhatja, ha tanáraik viselkedésén észlelik a kiégés tüneteit. Kutatásunk célja egy olyan magyar nyelvű kérdőív létrehozása volt, amely képes mérni, hogy a tanulók mennyire és… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In terms of the links between school demands and academic motivation, a recent study showed that among high school students resources were positively related to both intrinsic and extrinsic academic motivation, while demands were not associated with them. On the other hand, motivation was negatively related to resources and positively related to demands (Jagodics et al, 2020).…”
Section: Academic Motivation and Burnoutmentioning
confidence: 96%
“…In terms of the links between school demands and academic motivation, a recent study showed that among high school students resources were positively related to both intrinsic and extrinsic academic motivation, while demands were not associated with them. On the other hand, motivation was negatively related to resources and positively related to demands (Jagodics et al, 2020).…”
Section: Academic Motivation and Burnoutmentioning
confidence: 96%